An Experimental Investigation into the Effect of Soap on Ignition and Combustion Characteristics of Single Droplets of Glycerol. Issue 9 (2nd September 2017) - Setyawan, Hendrix Y.; Zhu, Mingming; Zhang, Zhezi; Zhang, Dongke
ABSTRACT: The effect of soap on the ignition and combustion characteristics of single droplets of glycerol was studied experimentally. Soap was added into a pure glycerol, both as by-products of biodiesel manufacturing, at concentrations of 1 wt% to 5 wt%. A single droplet of glycerol with and without soap addition was suspended on the tip of a silicon carbide fiber and exposed to air at 1023 K in an electrically heated tube furnace. The ignition and combustion behavior of the droplet was recorded using a CCD camera and the ignition delay time, burnout time, and burning rate were then estimated. A flame emission spectrometer was used to identify the presence of sodium in the flame. It was found that combustion of the glycerol droplets with soap addition occurred in a two-stage manner: (1) the first stage where glycerol preferentially was evaporated and burned and (2) the second stage where soap was evaporated and burned. This resembled that of bi-component droplets with vastly different volatilities. The addition of soap in the glycerol slightly reduced the ignition delay time and shortened burnout time of the droplets. The burning rate of glycerol was greater with increasing soap content in glycerol. Sodium ions were detected to present in the flame of glycerol droplets with soap additions. The release of sodium ions into the flame promoted the combustion rate of the fuel vapor.